Implanting Impella 5.5 under Local Anesthesia - Eghbalzadeh, Kaveh; Wahlers, Thorsten C.W.; Deppe, Antje Christin (The Thoracic and Cardiovascular Surgeon, 2023)
Background Surgically implanted Impella 5.5. delivers full cardiac support and left ventricular unloading for patients with heart failure. So far, the Impella device is implanted under general anesthesia (GA).Material and Methods A total of n = 3 critically ill patients presented with acute heart failure in need of cardiac support. All patients suffered cardiogenic shock of varying etiology. Due to hemodynamically unstable conditions, GA was avoided. All implantations were performed solely under local anesthesia (LAS) without any regional anesthesia.Results All implantations were performed successfully under LAS with 60 mL of mepivacaine of 2% solution and ropivacaine of 1% solution (50:50 ratio). All devices were placed from the right axillary artery. One patient needed hematoma evacuation several days after surgery. No other Impella-related complication was observed.Conclusion A surgical implantation of the Impella 5.5 device under LAS is feasible and safe. Despite the small number of cases, no disadvantage can be described at the present moment. Our series should encourage physicians to perform the procedure under LAS.
Keywords: circulatory assist devices; heart failure; transplantation; heart; cardiomyopathy